The Use Of Brown Rice Milk In The Making Of Milk Pie - Ghini Kunthala Devi; Ita Karnita; Farhan Hamdika (Gastronomy Tourism Journal, 2022)
Snack is defined as eating that occurs between the three substantial meals of the day, is convenient, and may be consumed promptly. A pie is a sort of delicacy that is shaped like a cake and filled with cream. Pie is a popular form of pastry in the United States. This roasted dish has been around since ancient Egypt. Meanwhile, pies were frequently used in Roman and medieval periods to wrap meat and other ingredients to keep them wet during cooking. Pies are cakes that are filled with cream, jelly, and other ingredients. Tarte (French) or pie (American), known as pai in Indonesia. The author will employ an experimental research method in the creation of this final project. The goal of this study was to compare the flavor of cow's milk pie to brown rice milk pie, to determine the shelf life of manufacturing cow's milk pie with brown rice milk pie, and to compute the cost of making cow's milk pie with brown rice milk pie.